Effects of aspect ratio of footings on bearing capacity for geogrid-reinforced sand over soft soil. Issue 4 (18th April 2017) - Saha Roy, S.; Deb, K.
Abstract : Model plate load tests of rigid rectangular footings of different aspect ratios resting on sand overlying soft soil with or without a layer of geogrid at the interface are presented. The width ( B ) and length ( L ) of the footings are chosen so that the L / B ratio (aspect ratio) is varied as 1.0, 1.5, and 2.0. The study aims to investigate the effects of the aspect ratio of the rectangular footings and the thickness of the sand layer on bearing capacity, settlement characteristics, load-spread angle, and sizes of geogrid layer (at optimum sand thickness). The strain distribution along the reinforcement is also studied. Based on the test results, an analytical method is proposed to calculate the load carrying capacity of rectangular footings resting on reinforced or unreinforced sand over soft soil. It is found that the optimum sand thickness to footing width ratio is not dependent on the aspect ratio of the rectangular footings. However, the optimum sizes of geogrid reinforcement increase with an increase in aspect ratio of the footings. Also, the load-spread angle increases with an increase in aspect ratio. It is also observed that the load-spread angle in the lengthways direction of a footing is smaller than that in the widthways direction, and it is more pronounced in the case of reinforced soil compared to unreinforced soil.